(untitled) (REICE: Revista Electrónica de Investigación en Ciencias Económicas, 2016)
The study was performed to analyze the survival strategies, socioeconomic employed in the past two decades by the indigenous community of San Andrés de Bocay. It has a qualitative approach. In education there is an enrollment of 2059 students, the retention rate is 80%, the illiteracy rate is 27% and 90% of indigenous view that education is regular. Attending the health center monthly thousand (1,000) people, 70% believe that health care is regular and the drug received covers 70% of needs. The economic structure is represented mainly by subsistence agriculture, 90% of the workforce is engaged in this activity. The form of ownership is communal, it is inherited and 95% of families own land, the lack of this resource may become factor of inequality and poverty. The average income per person is 1.1 to 1.7 dollars a day and 25% of people consider emigration help overcome poverty. REICE Vol.3(6) 2015: 92-121